Bacillus cereus Typhlitis in a Patient with Acute Myelogenous Leukemia: A Case Report and Review of the Literature - James D. Denham; Sowmya Nanjappa; John N. Greene (Case Reports in Infectious Diseases)
Bacillus cereus is a Gram-positive rod that is now recognized as a rare cause of frank disease in the neutropenic hematologic malignancy patient. Because this pathogen is rarely isolated in clinical specimens, no large studies exist to guide the management of these acutely ill patients. Individual case reports and case series exist in the literature describing various clinical manifestations of B. cereus in the neutropenic patient including bacteremia/septicemia, pneumonia, meningitis/encephalitis, hepatic abscesses, and gastritis. In this report, we describe a case of typhlitis caused by B. cereus in a 74-year-old female with recently diagnosed acute myelogenous leukemia (AML), and we summarize the available English language literature to draw tentative conclusions regarding the clinical manifestations of this organism.